To simplify the expression \(\sqrt[3]{-72}\), you can factor \(-72\) into its prime factors.
\[ -72 = -1 \times 2^3 \times 3^2 \]
Now, apply the cubic root:
\[ \sqrt[3]{-72} = \sqrt[3]{-1 \times 2^3 \times 3^2} \]
Breaking it down further:
\[ \sqrt[3]{-1} \times \sqrt[3]{2^3} \times \sqrt[3]{3^2} \]
Calculating each term, we get:
- \(\sqrt[3]{-1} = -1\)
- \(\sqrt[3]{2^3} = 2\)
- \(\sqrt[3]{3^2} = \sqrt[3]{9}\) (this cannot be simplified further)
Putting it all together:
\[ \sqrt[3]{-72} = -1 \times 2 \times \sqrt[3]{9} = -2\sqrt[3]{9} \]
So, the simplified form of \(\sqrt[3]{-72}\) is:
\[ -2\sqrt[3]{9} \]